STUDIES ON HELICOBACTER PYLORI IN ASYMPTOMATIC CHILDREN - MOHANKUMAR PANDURANGAN, (International Journal of Pharma and Bio Sciences, 2015)
This study has been planned to know the seroprevalence of Helicobacter pylori infection among children attending the paediatric department with complaints not related to gastro intestinal tract. Serum samples obtained from children of both sexes aged between 2 years to 16 years will be tested for anti - Helicobacter pylori antibodies of IgG class by quantitative ELIZA test. Results: It is observed that, female children acquired infection at an early age of 2-3 years while male children became infected only after 3 years. There is a steady increase in the age related sero prevalence among both the sexes and by the age of 12 years about 50 children of both sexes have acquired infection. Most of the seroprevalence children were from low socio-economic status .Conclusion: Helicobacter pylori is recognised as a risk factor for gastric carcinoma and lymphoma. Though the disease is acquired in childhood it is asymptomatic during childhood and produce manifestations in the later part of the life. As Helicobacter pylori infection is curable, an early diagnosis and treatment in childhood will prevent the late consequences of the disease in future life.